Physicochemical characterization of mixtures from organic waste for using as agricultural substrates (Bioagro, 2020)
The use of locally available materials that meet appropriate physicochemical characteristics represents an alternative to replace commercial substrates of high cost and negative environmental impact. The objective was to characterize organic material mixtures that are available in Yucatan, Mexico, to identify their potential as substrates. Pine chips (VP) and raw sawdust (AP) were mixed with different percentages of henequen bagasse (BH) and coir dust (PC), as follows: 20BH+80AP; 30BH+70VP; 20PC+80AP; 20PC+80VP; 20PC+40AP+40VP; and 20BH+40AP+40VP. Additionally, a peat-based commercial substrate was used. Particle size, bulk density, total porosity, air-water relations, pH, electrical conductivity (CE), organic matter content, biological activity, cation exchange capacity (CEC) and the N, K+, Ca2+, Mg2+ and Na+ content was measured. All the mixtures showed high total porosity. Those containing AP+PC had particle size and water retention capacity similar to the commercial substrate, and the 20PC+80AP and 20BH+40AP+40VP mixtures surpassed it in the percentage of total available water. The 30BH+70VP mixture was superior to all the mixes in the contents of N, P, K+, and Ca2+. All the mixtures showed pH slightly higher than the recommended maximum limit (6.5), CE with values lower than 1.5 dS∙m-1, CEC  with  mid-levels (10  a 15 meq∙100 g-1)  and  low  CO2  production  (3.5 to 4 µmol∙m-2∙s-1)  that  increased  in  the  mixtures  with BH  up  to  9.77 µmol∙m-2∙s-1.  Therefore,  all mixtures  have   appropriate   physical   and   chemical   characteristics  to  consider  them  as alternatives for agricultural substrate.
Keywords: Biological activity; bulk density; granulometry; porosity